(untitled) (Global Journal of Human-Social Science, 2020)
This paper examines Nigeria’s national security imperatives with a focus on the role of the country’s correctional service in the management of Violent Extremist Offenders(VEOs).It draws its data from primary and secondary sources. Doing this, it adopts the interpretative framework of analysis. Management of violent extremism in Nigeria is shown to be based on the eclectic approach involving religious leaders, the National Orientation Agency, and the Nigerian Correctional Service (NCS) under the supervision of the Office of the National Security Adviser (ONSA). The study reveals that the deradicalization programme being handled by the correctional service lacks post-release component, identified in the Standard Minimum Rules for the Treatment of Offenders as a significant element of inmates’ reintegration. Detention and treatment of violent extremist offenders by the Nigerian army also inhibit effective rehabilitation of this category of offenders because such activity is not core to the mandate of the army.